Association of HLA-DPB1, NLRP10, OVOL1, and ABCC11 with the axillary microbiome in a Japanese population. Issue 2 (February 2022) - Kutsuwada, Yukinobu; Yokota, Kazuha; Yoshida, Ken; Tsuda, Hidetoshi; Watanabe, Kazuhisa; Matsumoto, Ayumi; Iwamoto, Sadahiko
Highlights: HLA‐DPB1*19:01, rs878860 C, and the rs17822931 C allele decreased the relative abundance of Corynebacterium . HLA‐DPB1*09:01, *14:01, *19:01, rs878860 C, rs10791824 G, and the rs17822931 C allele increased that of Staphylococcus. HLA‐DPB1*04:01, *05:01, and the rs17822931 C allele increased the axillary E3M2H intensity. Abstract: Background: The distinct diversity of the human skin microbiome depends not only on the body site but also the individual. Host-commensal interactions have been described for the gut microbiome, but little is known about the epidermal microbiome. Objective: The present study investigated whether genetic variants associated with skin traits affect the axillary microbiome. Methods: Eight skin trait-related single nucleotide polymorphisms and HLA-A, -B, -C, and –DPB1 were genotyped in 186 Japanese males. From axillary swabs, the intensity of a representative axillary odor, trans (E) isomer of 3-methyl-2-hexenoic acid (E3M2H), was quantified with gas chromatography-tandem mass spectrometry analysis, the diversity of the axillary microbiome was evaluated with a 16 s rRNA metagenomic approach, and the association of these characteristics was assessed statistically. Results: A risk allele for atopic dermatitis of rs878860 in NLRP10 and the allele for wet earwax of rs17822931 in ABCC11 decreased the relative abundance of Corynebacterium . Conversely, these alleles increased the relative abundance of Staphylococcus. Metagenomic analysis revealed that β-diversity showed significant dissimilarity at the weighted Unifrac distance between minor allele carrier and non-carrier groups in HLA‐DPB1*05:01, rs17822931, and rs878860. HLA‐DPB1*04:01, HLA‐DPB1*05:01, and rs17822931 were associated with E3M2H. Conclusions: We identified novel candidate loci associated with the axillary microbiome and malodor.